Upaya Mengembangkan Kreativitas Anak Usia 5-6 Tahun melalui Permainan Eksplorasi - Ade Tursina (Aṭfāluna: Journal of Islamic Early Childhood Education, 2018)
The problem in this research was: (1) low of creativity in 5-6-year-old children in TK Sandhy Putra Medan, (2) education system that focuses more on academic ability such as reading, writing and counting, (3) lack of facilities that can develop the creativity of children, (4) Children are less motivated by teachers in developing their creativity. This research aims to determine the creativity development of 5-6-year-old children by using the exploration game “sand play" in TK Sandhy Putra Medan. This type of research was classroom action research conducted in 2 cycles, whereby each cycle is performed 2 times a meeting. In each cycle is done through 4 stages, namely planning, implementation, observation and reflection. The data collection tools used are observations. The subject of this study was 5-6-year-old children in TK Sandhy Putra Medan, a total of 20 children consisting of 11 daughters and 9 boys. While the object of this research is developing the creativity skills of children aged 5-6 years in the TK Sandhy Putra Medan. The instrument in this research is the observation sheet for the development of children's creativity with the following indicators: great curiosity, high originality, imaginative, diligent and not easily bored learning, dare to take risks, and full of initiation.